2013
DOI: 10.1007/978-3-642-39091-3_15
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Capacities as Imprecise Possibilities

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. Abstract. This paper studies the structure of qualitative capacities, that is, monotonic set-functions, when they range on a finite totally ordered scale equipped with an order-reversing map. These set-functions correspond to general representations of uncertainty, as well as importance levels of groups of criteria in multicriteria decision-making. More specifically, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Important special cases of capacity are possibility and necessity measures. 1 This paper is based on and extends two previous conference papers [11,21].…”
Section: Qualitative Capacities and Möbius Transformsmentioning
confidence: 95%
See 1 more Smart Citation
“…Important special cases of capacity are possibility and necessity measures. 1 This paper is based on and extends two previous conference papers [11,21].…”
Section: Qualitative Capacities and Möbius Transformsmentioning
confidence: 95%
“…It can be shown that the property is equivalent to the existence of two necessity measures such that ∀A, γ (A) = max(N 1 (A), N 2 (A)) (see [21] for a detailed proof of this case). For instance, the capacity in Example 1 is 2-adjunctive.…”
Section: ∀A B C Min γ (A) γ (B) γ (C) ≤ Max γ (A ∩ B) γ (B ∩ Cmentioning
confidence: 99%
“…In practice, we can translate this information by m(A 1 ) ≥ · · · ≥ m(A n ), from which it is easy to extract extreme points. Sets of possibility measures have also been recently investigated from a qualitative perspective by Dubois, Prade, and Rico (2013).…”
Section: Possibility Measuresmentioning
confidence: 99%
“…In the qualitative setting, a monotonic set-function can always be viewed as the lower bound of a set of possibility measures (µ(A) = min n i=1 Π i (A)) which comes down to representing epistemic states expressed by µ as a set of possibility distributions over Ω (e.g. corresponding to several agents) [48].…”
Section: Uncertainty Semanticsmentioning
confidence: 99%